Consuptiom phytoestrogen flaxseed alters lipid profiles of menopausal: what is evidence? - Guerra, Thais Rezende Bessa; Boaventura, Gilson Teles (Journal of Health Care, 2016)
Introduction: Flaxseed is a beneficial phytoestrogen that has omega 3, lignans, and fiber that promotes hypolipidemic action. In the period of menopause women are more susceptible to changes in lipid metabolism, due to estrogen deprivation, and develop a lipid profile highly favorable to atherogenesis. In clinical practice the flaxseed oil and flaxseed in natura have been widely consumed. Objective: To review the literature evidence on the influence of phytoestrogen flaxseed in its different forms of intake in natura and oil on the lipid profile, with emphasis on menopausal and postmenopausal women. Methods: We analyzed 11 studies using as criteria: controlled clinical trials, randomized, crossover, international, and published between 1997 and 2015. This review used data from 360 menopausal and postmenopausal women, aged between 41 and 73 years who consumed this phytoestrogen. Conclusion: Studies have demonstrated short periods of consumption of this phytoestrogen and quantity ranging from 20 to 40 mg/day, evidence suggests that the consumption of flaxseed in natura have a positive influence on reduction of plasma levels of total and LDL cholesterol as compared to consumption of linseed oil.